1990
DOI: 10.1271/bbb1961.54.2553
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of the saponin fraction obtained from Asparagus officinalis L. and its active principle.

Abstract: Antifungal activity was detected in the crude saponin fraction obtained from the bottom cut of Asparagus officinalis L. This activity was specific to certain fungi, for example Candida, Cryptococcus, Trichophyton, Microsporum and Epidermophyton. Attempts were made to isolate the active principles from this fraction; in this way a new saponin (AS-1) was isolated, and its structure was estimated to be 3-0-[{/?-D-glucopyranosyl(l-åº2)}{)5-D-xylopyranosyl(l-åº 4)-/?-D-glucopyranosyl]-(255'),5/?spirostan-3/J-ol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 1 publication
2
33
0
1
Order By: Relevance
“…Previous studies have shown that saponin compounds act as defensive substances against soil-borne stresses and/or diseases (Bouarab et al, 2002;Hughes et al, 2004;Osbourn, 1996;Shimoyamada et al, 1990Shimoyamada et al, , 1996Wu et al, 2005); therefore, biosynthesis of certain saponin compounds is likely to be regulated by soilborne stresses and/or diseases. Meanwhile, jasmonate (JM) and its methyl ester (methyl jasmonate [MeJM]) are regarded as plant hormones and are also known to trigger defensive reactions against some stresses and diseases (Creelman and Mullet, 1997;Wasternack and Parthier, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that saponin compounds act as defensive substances against soil-borne stresses and/or diseases (Bouarab et al, 2002;Hughes et al, 2004;Osbourn, 1996;Shimoyamada et al, 1990Shimoyamada et al, , 1996Wu et al, 2005); therefore, biosynthesis of certain saponin compounds is likely to be regulated by soilborne stresses and/or diseases. Meanwhile, jasmonate (JM) and its methyl ester (methyl jasmonate [MeJM]) are regarded as plant hormones and are also known to trigger defensive reactions against some stresses and diseases (Creelman and Mullet, 1997;Wasternack and Parthier, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of six individual saponins occurring in asparagus spears has been identified (Fenwick and Oakenfull 1983;Kawano et al 1977;Shao et al 1996;Shimoyamada et al 1990Shimoyamada et al , 1996Wang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2005) reported that osmotic stress treatment activated saponin biosynthesis in cultured cells of Panax ginseng. Shimoyamada et al (1990Shimoyamada et al ( , 1996 reported that saponin compounds AS-1 and AS-2-I, found in asparagus, showed antifungal activity on some species of fungi. Therefore, saponin biosynthesis regulation in white asparagus spears may be associated with an antistress and/or defensive action against pathogen or insect attack.…”
Section: Discussionmentioning
confidence: 99%